The Explanation of the Interpretation Method and its Influence over Social Sciences with an Emphasis on Ayat Allah Javadi Amoli’s Thoughts - Reza Mollaie; Hamid Parsaniya (حکمت اسرا)
The interpretation method in Transcendent Theosophy has some properties that when applied to social phenomena give an especial description of them. Indicating the fundamentals of interpretation method in Transcendent Theosophy, we will explain two kinds of interpretation, that is, existential and conceptual interpretations. Then we will formulate the stages of interpretation method according to Transcendent Theosophy and show how each kind of interpretations go through two stages to reach the inner face of the phenomena: breaking the veil and turning back to the origin. Applying this method to understand the social phenomena involves that the social scientist after breaking the veil get through to the inner face of the social phenomenon. In the light of this method, it becomes clear that the inner face of the social phenomena are their being sing, symbol, and Ayah. Social phenomena in their Inner faces are signs and symbols that show the names and attributes of the divinity in the scene of human communities and their relations. So, understanding the social phenomena, real or value-dependent, will be feasible only in the light of the divine names dominating them.